Computed Tomography versus Optical Scanning: A Comparison of Different Methods of 3D Data Acquisition for Tooth Replication. - Kulczyk, Tomasz; Rychlik, Michał; Lorkiewicz-Muszyńska, Dorota; Abreu-Głowacka, Monica; Czajka-Jakubowska, Agata; Przystańska, Agnieszka (BioMed Research International, 2019)
Objectives. The study aimed to compare the accuracy of different methods of data acquisition and data reconstruction and to assess their usefulness for 3D printing of tooth replicas. Methods. 3-dimensional models of molar and canine teeth obtain utilizing CBCT examination with different protocols, and optical scanning was compared with models derived from micro-computed (micro-CT) examination using Geomagic Studio Qualify software. A pairwise comparison of 3D models with analysis of standard deviation and the value of the mean distance of given surfaces was performed. Results. Standard deviation and the value of the mean distance were lowest for optical scanning followed by CBC in high and standard resolution in all tested protocols. Models, obtained with high-resolution CBCT protocols, of teeth in and outside of alveolar bone showed similar average distance parameters, but standard deviation parameter was significantly lower for models of teeth scanned outside of the socket. Good surface representation on all models was seen at relatively smooth areas while in areas of high changes in the geometry CBCT based models performed inferiorly to those obtained from an optical scanner. Conclusions. In case of teeth of noncomplicated texture, independently from a position (within or outside the alveolar socket), the high-resolution CBCT seems to be a sufficient method to obtain data for 3D printed tooth replica. Optical scanning performs better when a detailed replica is necessary.